Altered Progesterone Receptor Isoform Expression in Endometrial Cells: A Preliminary Immunohistochemical Study in Endometriosis - Kathryn Coyne; Chloe Van Dorn; Sung Tae Kim; Joseph Findley; Rebecca Flyckt; Sam Mesiano; Rachel Weinerman (Journal of Clinical Medicine, 2026)
Background/Objectives: The objective of this exploratory study was to test the hypothesis that endometriosis is associated with altered abundance and cellular location of nuclear progesterone receptor (PR) isoforms in eutopic endometrium. Methods: Immunohistochemistry (IHC) was used to compare total PR (PR-A/B), PR-B, and pSer344/345-PR staining in endometrium from patients with and without endometriosis and between eutopic endometrium and ectopic endometriotic lesions in patients with endometriosis. Reproductive-age female patients undergoing laparoscopy for endometriosis (n = 10), or for other indications and without a diagnosis of endometriosis (n = 10), were included in this case–control study. Results: Eutopic endometrium from patients with endometriosis demonstrated increased total PR (PR-A/B) staining relative to PR-B staining compared with patients without endometriosis; a similar staining pattern was observed in ectopic lesions. Because PR-A was not measured directly and the total PR and PR-B antibodies may differ in affinity and dynamic range, these findings provide indirect evidence of altered relative PR isoform abundance rather than direct demonstration of a PR-A-dominant state. pSer344/345-PR staining did not differ significantly between groups, although a nonsignificant trend toward higher staining was observed in endometriosis. Conclusions: These preliminary findings support further study of PR isoform balance and site-specific phosphorylation in progesterone resistance associated with endometriosis.